e-Research in the life sciences: from invisible to virtual colleges - Power, LA (2011)
e-Research in the Life Sciences examines the use of online tools in the life sciences and finds that their use has significant impact, namely the formation of a Scientific/Intellectual Movement (SIM) (Frickel & Gross, 2005) complemented by a Computerisation Movement (CM) (Kling & Iacono, 1994) which is mobilising global electronic resources to form visible colleges of life science researchers, who are enrolling others and successfully promoting their open science goals via mainstream scientific literature. Those within this movement are also using these online tools to change their work practices, producing scientific knowledge in a highly networked and distributed group which has less regard for traditional institutional and disciplinary boundaries. This thesis, by combining ideas about SIMs and CMs, fills a gap in research that is typically confined to treating new tools as a part of scientific communication or in specialist areas like distributed collaboration but not in terms of broader changes in science. Case studies have been conducted for three types of online tools: the scientific social networking tool FriendFeed, open laboratory notebooks, and science blogs. Data have been collected from semi-structured interviews, and the online writings of research participants. The case studies of exemplary use by scientists of the web form a baseline for future studies in the area. Boundaries between formal and informal scholarly communication are now blurred. At the formal level, which peer-reviewed print journals continue, many academic publishers now also have online open access, frequently in advance of print publication. At the informal level, what used to be confined to water-cooler chat and the conference circuit is now also discussed on mailing lists, forums and blogs (Borgman, 2007). As these online tools generate new practices they have potential to affect future academic assessment and dissemination practices.